Short-term sprint-interval training improves insulin sensitivity in young adult humans - Johnson, Tyler Kass, author; Bell, Christopher, advisor; Hickey, Matthew S., advisor; Miller, Benjamin F., committee member; Melby, Christopher L., committee member (Colorado State University. Libraries, 2009)
Habitual endurance exercise has been shown repeatedly to increase insulin sensitivity, one of the principal determinants of blood glucose control. Many adults however, choose not to participate in this type of exercise, citing insufficient time as a perceived obstacle. A recent study has described improved blood glucose control post-consumption of a glucose beverage following 2-weeks of sprint-interval training (SIT), implying that SIT may increase insulin sensitivity. PURPOSE: Using the gold standard measure, the hyperinsulinemic euglycemic clamp technique, we investigated the hypothesis that SIT will increase insulin sensitivity. METHODS: 12 healthy, sedentary or recreationally active adults (age: 27 ± 3 yr; body mass index: 26.2 ± 1.4 kg/m2; VO2peak: 36.0 ± 3.3 ml/kg/min (mean ± SE)) completed 6 sessions of repeated (4 to 7) 30-second bouts of extremely high-intensity cycle ergometer exercise (i.e. a Wingate protocol) over 14 days. Prior to and 72 hours following completion of SIT the glucose infusion rate (GIR) required to maintain a blood glucose concentration of 90 mg/dL during a standardized infusion of insulin was determined. In order to quantify the effect of the most recent SIT bout on insulin sensitivity, GIR was determined in 7 adults (25 ± 1 yr; 25.7 ± 1.4 kg/m2; 37.1 ± 4.3 ml/kg/min) prior to and 72 hours following a single bout of SIT. Finally, in order to establish the day-to-day variability in GIR, 9 adults (23 ± 2 yr; 26.8 ± 1.6 kg/m2, 33.3 ± 2.2 ml/kg/min) served as a sedentary control. RESULTS: Compared with baseline, insulin sensitivity was increased following short-term SIT (GIR: 6.2 ± 0.7 vs. 8.0 ± 0.8 mg/kg/min; P = 0.02) but was unchanged following a single bout of SIT (9.7 ± 1.3 vs. 10.7 ± 1.4; P = 0.43) or a period of inactivity (7.9 ± 0.9 vs. 8.3 ± 1.0; P = 0.38). Regardless of intervention, blood glucose concentration at the end of the hyperinsulinemic euglycemic clamp, body mass and fasting blood glucose concentration remained unchanged (all P > 0.2), with the exception of a small increase in fasting glucose following a single bout of SIT (73.6 ± 1.8 vs. 75.8 ± 1.3 mg/dL; P = 0.01). CONCLUSION: These data, collected using the gold standard hyperinsulinemic euglycemic clamp technique, suggest that short-term SIT is a viable alternative to endurance training as a strategy to improve insulin sensitivity.
Department Head: Richard Gay Israel.